2004
DOI: 10.1291/hypres.27.393
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Intake and Cardiac Sympatho-Vagal Balance in Young Men with High Blood Pressure

Abstract: We have previously reported that a high sodium intake increases sleep-time blood pressure (BP) in young men. However, there are cases in which this relation does not apply. To account for them, we investigated the relation between sodium intake and cardiac sympatho-vagal balance (SVB) in young men with high BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…Epidemiologic studies have observed a relationship between dietary NaCl intake and blood pressure (12)(13)(14)(15)(16). The National Nutrition Survey shows that approximately oneeighth of the dietary salt intake in the Japanese diet comes from miso (17).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies have observed a relationship between dietary NaCl intake and blood pressure (12)(13)(14)(15)(16). The National Nutrition Survey shows that approximately oneeighth of the dietary salt intake in the Japanese diet comes from miso (17).…”
Section: Introductionmentioning
confidence: 99%
“…The great influence of daily mental and physical activities exerted on these values means that they have poor reproducibility. Therefore, ambulatory BP monitoring (29,30) or home BP measurement (31-33) has been used recently in ordinary clinics and many studies. Base BP (BP0, i= 0), on the other hand, is the minimum value occurring at night during sleep, and has slight day-to-day fluctuation (2.4±1.8 mmHg for MBP) (10).…”
Section: Discussionmentioning
confidence: 99%
“…6,12 A computer automatically detected base BP values corresponding to the minimum HR value. [5][6][7] Body motion (activity) was measured by an acceleration pickup sensor. Cumulative values for 1-min periods were recorded at 18-ms intervals at frequencies ranging from 1 to 10 Hz in the vertical direction (z axis), a sensitivity of 4.1 Â 10 À3 m/s 2 bit.…”
Section: Methodsmentioning
confidence: 99%
“…5,6 The minimum sleep-time BP (BP0: base BP) has been reported to correlate with sodium intake. 7 Furthermore, systolic BP0 (SBP0) demonstrated a significantly higher r value (r ¼ 0.83) with body fat-corrected mean electrocardiogram (ECG) voltage/body surface area than the mean daytime systolic BP (SBP) in hypertensives. 8 However, the implications of BP0 in healthy people remain unclear.…”
Section: Introductionmentioning
confidence: 99%